Tracks and Traces: Exploring the World of Graffiti Writing trough Visual Methods Book review - Neves, Pedro Soares (GSA - Graffiti and Street Art, 2023)
This review examines Peter Bengtsen's Tracks and Traces, a noteworthy exploration of graffiti writing through visual methods. The book presents a compelling perspective on graffiti as a form of personal expression, delving into its intricate unique details. Bengtsen's work stands out for its exceptional publication quality, for example with pages that unfold for big sized images, providing readers with a visually rich and engaging experience. The strength of the book lies in its well-referenced content, firmly grounded in experimental applied research. Bengtsen builds his arguments on a solid foundation, making the publication a valuable resource for those seeking a comprehensive understanding of graffiti from the visual methods point of view. Moreover, the book introduces transferable methodological approaches that contribute to its broader relevance beyond the immediate subject matter. A paramount hypothesis explored in the book revolves around the refined attentiveness of graffiti practitioners to the city environment. Bengtsen posits that individuals engaged in graffiti develop a heightened awareness of and connection to the urban landscape. This hypothesis adds a significant layer to the discourse on graffiti, shedding light on the symbiotic relationship between graffiti and the city. One of the commendable aspects of Tracks and Traces is its accessibility to readers new to graffiti as a subject. Bengtsen effectively navigates the intricacies of graffiti culture, making the book approachable without compromising on depth. The inclusion of visual methods enhances comprehension, allowing readers to grasp the essence of graffiti writing even if they are unfamiliar with the topic. In summary, Tracks and Traces by Peter Bengtsen emerges as a valuable contribution to the study of graffiti writing. Its focus on personal expression, high publication quality, rigorous research methodology, and accessible presentation makes it a recommended read for both scholars and newcomers interested in exploring the world of graffiti through a visual lens.